Ode to grapefruit : how James Earl Jones found his voice - Lavelle, Kari (Alfred A Knopf, 2024)
Before legendary actor James Earl Jones was recognized for his memorable, smooth voice, he was just James -- a stutterer who stopped speaking for eight years as a child...and ultimately found his voice through poetry.